Human papilloma virus (HPV) is not implicated in the etiology of Warthin's tumor of the parotid gland. (September 2013) - Teymoortash, Afshin; Bohne, Franziska; Jonsdottir, Thuridur; Hoch, Stefan; Eivazi, Behfar; Roessler, Marion; Werner, Jochen A.; Mandic, Robert
Abstract Conclusion: The lack of human papilloma virus (HPV) sequences as well as potential HPV-activated cells such as cells that would be p16- and Ki-67 positive does not support a role of HPV in the pathogenesis of this lesion. Objective: The exact etiopathogenesis of Warthin's tumor of the parotid gland is still unclear. The aim of the present study was to evaluate if HPV could play a role in the development of this parotid lesion. Methods: Tissue samples from 40 Warthin's tumors of the parotid gland were investigated by PCR followed by in situ hybridization. The immunohistochemical expression of p16 and the dual immunostaining of p16 and Ki-67 were evaluated in all samples. Results: Strong and diffuse p16 immunoreactivity was found in 7 of the 40 cases (17.5%). In situ hybridization showed a diffuse episomal signal in those samples. However, PCR could not reliably detect the presence of HPV genes. Furthermore, p16-expressing epithelial cells were mostly negative for the proliferation marker Ki-67.